Evaluation of potato varieties in the field resistance to Colorado beetle - Oleinik, T.N.; Podberezko, B.N.; Koval, V.S. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2016)
When covering the results of evaluation of potato varieties domestic breeding for resistance to Colorado potato beetle (Leptinotarsa decemlineata Say.). The effect of resistant potato varieties on the physiological state of the Colorado potato beetle, and the degree of damage to the leaf surface of plants at different periods of vegetation. Allocated relatively resistant to Colorado beetle of potato varieties: Vedruska, Vimir, Vodograi, Glazurna, Serpanok, Povin.